HISTORIOGRAFI GLOBALISASI BATIK MASA KOLONIAL DAN TANTANGAN GLOBAL ERA KONTEMPORER - Adisasmito, Nuning Damayanti (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
With regard to the long history of the creation of Batik Indonesia and its development, batik technique becomesone that is recognized as the world cultural heritage. UNESCO on October 2 , 2009 recognized belonging of Batik to the nation of Indonesia which became world heritage, then October 2nd at once also celebrated as National Batik Day. This is the work of many parties and government support. Batik is a product of indigenous culture of Indonesia, especially made by the people of Java Island, but now scattered centers of batik industry almost throughout theIndonesian archipelago, not only in Pekalongan, Solo, Yogyakarta, Madura, Tasikmalaya, Cirebon, Garut. This fact adds to the rich variety of Batik Nusantara.